2015
DOI: 10.1007/s12205-015-1104-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of oil palm shell lightweight aggregate concrete containing palm oil fuel ash as partial cement replacement

Abstract: The increasing in greenhouse gas emissions, as well as solid waste disposal from the cement manufacturing industry and the Malaysian palm oil industries respectively contributes towards the undesirable 6°C Scenario envisioned by the International Energy Agency. The utilization of Palm Oil Fuel Ash (POFA) as partial cement replacement in the production of Oil Palm Shell (OPS) Lightweight Aggregate Concrete (LWAC) would significantly reduce cement consumption and amount of disposed landfill waste. In this invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 19 publications
2
8
0
1
Order By: Relevance
“…Here, the fibres and the cement matrix achieved high compaction, which resulted in good mix homogeneity with 0.45% fibre inclusion. This finding is also supported by Muthusamy & Zamri (2016), who proved that compressive strength and bulk density are slightly enhanced with low fibre content ranging between 0.3% to 1.5%.…”
Section: Compressive Strengthsupporting
confidence: 76%
“…Here, the fibres and the cement matrix achieved high compaction, which resulted in good mix homogeneity with 0.45% fibre inclusion. This finding is also supported by Muthusamy & Zamri (2016), who proved that compressive strength and bulk density are slightly enhanced with low fibre content ranging between 0.3% to 1.5%.…”
Section: Compressive Strengthsupporting
confidence: 76%
“…(Munir et al, 2015) discovered the compressive strength was reduced until 40% when the 50% POFA as cement replacement added into foamed concrete while other researcher (Tangchirapat & Jaturapitakkul, 2010) found strength of concrete reduced to 84% than control mix with cement replacement 30% POFA. However, other researcher (Momeen et al, 2016;Muthusamy & Zamri, 2016) found use of POFA as partial cement replacement amount 10% to 15% improved the compressive strength of concrete.…”
Section: Previous Studies On Pofamentioning
confidence: 92%
“…At 0.45% volume fraction of EFB fibre, the fibres and the cement matrix attained high compaction, which resulted in good mix homogeneity. Compressive strength and bulk density are slightly enhanced with low fibre content ranging between 0.20% to 0.45% [24]. High addition of natural fibre into the LFC mixture, especially the low densities, will retard the hydration process, thus resulting in low strength of LFC although it will gain strength after a certain age [25].…”
Section: Methodsmentioning
confidence: 99%